The impact of irrigation on agriculture productivity: Evidence from Sri Lanka - Dunusinghe, P. (University of Colombo, Sri Lanka., 2019)
Sri Lanka has a great history of irrigation dating back to 500 BC. During the post-independence era, successive governments launched a number of major and minor irrigation projects aiming at, among other targets, agricultural and rural development. Nevertheless, irrigation-productivity nexus has limitedly been investigated in the context of Sri Lanka. The overall objective of this study is to examine the impact of irrigation on agricultural productivity. This study examines the impact of irrigation on selected crops, namely paddy and maize, by estimating
Keywords: agriculture, irrigation, productivity, production function, Sri Lanka